Different Effects of a By‐product From Olive Oil Extraction on S‐Metolachlor and Bentazone Soil Fate. Issue 6 (29th December 2014) - Cañero, Ana I.; Cox, Lucía; Cabrera, Alegría; Cornejo, Juan
<x xml:space="preserve">Abstract</x> Bentazone and S‐metolachlor are herbicides widely used for the control of broad leaf weeds in crops such as corn and soybean. The effect of the addition to soils with different texture and organic matter content of an organic waste (OW) from oil olive production (alperujo) on different processes affecting behaviour of both herbicides was evaluated. Sorption of S‐metolachlor increased upon amendment. A six‐fold increase could be observed for Kd values on the sandy soil amended at 10% rate and a five‐fold increase on the soil with higher content on clay (48%) and same rate of OW (10%). The results revealed that although an increase in soil total pore volume was found upon amendment (from 210 to 266 mm3 g−1 in sandy (S) soil, from 215 to 251 in clayey (19% silt) (T) soil, and from 240 to 289 in clayey (50% silt) (E) soil), leaching of the herbicide S‐metolachlor was greatly reduced (from 61 to 3.5% in the S‐soil and from 37 to <1% in the clayey T‐soil) since its behaviour in soils is strongly affected by sorption processes. Bentazone leaching was only slightly delayed upon amendment. Half‐life of both herbicides also increased upon amendment. The greatest increase was observed with the higher rate of OW (10%) in the soils with higher content of clay (48% in T‐soil and 31% in E‐soil). A 17‐fold increase was observed for S‐metolachlor half‐life in T‐soil and a four‐fold increase for bentazone in E‐soil. Thus, the use of the by‐product from olive oil extraction can be a good strategy to reduce the off‐site movement of S‐metolachlor by increasing its soil sorption, and therefore the risk of water pollution can be diminished. However, the higher persistence of both herbicides in organic amended soils should be taken into account.